MITIGATION MODEL FOR RISK HANDLING IN ISLAMIC EDUCATION INSTITUTIONS - Hidayat, Rahmad; Widara, Yuyun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Every activity in life, including in educational institutions, is inevitably accompanied by risks. The risks are present in various components within educational institutions. Therefore, the management process of educational institutions must adhere to applicable laws, such as the Qur'an as a guide for Muslim individuals' lives, and the legal regulations of the country. The purpose of this article is to elucidate the methods of mitigating the risks of educational institutions based on the Qur'anic perspective. The article employs a qualitative approach with a literature study method to identify the most suitable risk mitigation methods for educational managers to mitigate the risks of their institutions. Risk mitigation is a logical and systematic method that involves identifying risks, determining attitudes and policies, establishing solutions, and conducting monitoring and evaluation for each activity or organizational process. To mitigate risks in educational institutions means to reduce the risk levels, both in terms of likelihood and impact, in every aspect of education.